Shaping the future of East Asian economic architectures : views of ASEAN - Pitakdumrongkit, Kaewkamol (2020)
The world has witnessed significant changes in its economic and strategic landscape since the Cold War era. In today’s multipolar system, states have a variety of partners that they can choose to engage. Also, globalization has not only deepened economic interdependency but also made several issues transnational. Increasing linkages heighten the importance of international cooperation to tackle existing problems. East Asia—comprised of the ten states in ASEAN, China, Japan, and South Korea—is no exception.